Threads of Life: micropolitics and macropolitics in Lygia Clark’s Caminhando proposition: micropolítica e macropolítica na proposição Caminhando de Lygia Clark - Magalhães, Thaís Fernanda Rocha; Azevedo, Maria Thereza de Oliveira (Revista do Colóquio, 2020)
The purpose of this article is to approach the work Caminhando (1963) by Brazilian artist Lygia Clark (1920 - 1988) weaving dialogues with authors such as Suely Rolnik (2019), Félix Guattari and Giles Deleuze (1996). Rolnik, offers us a reading that updates Caminhando based on the concepts of micropolitics and macropolitics, calling attention to the urgency in recognizing the articulation between such social spheres in the production of subjectivity. Caminhando helps us to make a cut in the Brazilian Visual Arts where it is possible to observe some embryonic processes of contemporary art: participation and conceptualism. Both of which lead us through the tangled threads of life when we try to make the gesture of cutting a ribbon made of paper, an daily object that in our reading supports the paradox between right and inside out, inside and outside as in Moebius’s bands.